2005
DOI: 10.1002/rcm.2030
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiresidue method for analysis of major Fusarium mycotoxins in corn meal using liquid chromatography/tandem mass spectrometry

Abstract: A sensitive and reliable liquid chromatography/electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) method has been developed to determine, in a single run, eight trichothecenes, three fumonisins, zearalenone and alpha-zearalenol, in corn meal samples. LC and MS conditions were varied to find the best compromise in terms of sensitivity and separation. An acceptable compromise was obtained using a C18 column thermostatted at 45 degrees C and a mobile phase gradient of methanol/water with 10 mmol/L fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 34 publications
8
60
1
Order By: Relevance
“…A similar phenomenon was reported by Groten et al (49) and Tajima et al (51), who observed additive effects on the inhibition of DNA synthesis when L929 fibroblasts were exposed to multiple Fusarium toxins (DON, NIV, T-2 toxin, ZEA, and FB1), though some synergistic interactions were also reported (49,51). Additive effects may occur when there is cooccurrence of more than one mycotoxin causing toxicity through the same mechanism of action (52). In our study, interactive effects, which have not been reported previously, were observed in mixtures containing NIV and FB1, though the reason for such interaction remains unknown.…”
Section: Discussionsupporting
confidence: 80%
“…A similar phenomenon was reported by Groten et al (49) and Tajima et al (51), who observed additive effects on the inhibition of DNA synthesis when L929 fibroblasts were exposed to multiple Fusarium toxins (DON, NIV, T-2 toxin, ZEA, and FB1), though some synergistic interactions were also reported (49,51). Additive effects may occur when there is cooccurrence of more than one mycotoxin causing toxicity through the same mechanism of action (52). In our study, interactive effects, which have not been reported previously, were observed in mixtures containing NIV and FB1, though the reason for such interaction remains unknown.…”
Section: Discussionsupporting
confidence: 80%
“…It has a number of inherent properties that are advantageous for this application, including high selectivity and sensitivity, minimization of sample cleanup steps, and easy and reliable identification and quantification of pesticide residues at even very low levels (Picó et al, 2006). A number of multiresidue methods using LC-MS/MS for residue determination have been reported (Jansson et al, 2004;Ortelli et al, 2004;Cavaliere et al, 2005;Sancho et al, 2005;Hernández et al, 2006;Chen and Chen, 2007;Mertz et al, 2007;Sannino, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Alassane-Kpembi et al (1) in a study on pigs. Synergistic interactions can occur at different stages in the same toxicity pathway, or when the presence of one mycotoxin increases absorption or decreases the metabolic degradation of another mycotoxin (27,28,6).…”
Section: Discussionmentioning
confidence: 99%